Ukrainian food journal. № 3 - National University of Food Technologies (My University, 2012)
An international scientific periodical for the publication of research results of experts in the field of food science, technology and technology, chemistry, economics and management. Міжнародне наукове періодичне видання для публікації результаті досліджень фахівців у галузі харчової науки, техніки та технології, хімії, економіки і управління.
Keywords: харчові науки; техніка; хімія; економіка; управління; экономика; управление; пищевые науки; техника; химия; chemistry; management; food science; machinery; economy